Ethics of Finitude: Nursing and the Palliative Approach in Geriatric and Forensic Psychiatry. (May 2020) - Skinner, Elise; Jacob, Jean Daniel; Vanderspank-Wright, Brandi; Wright, David Kenneth
There is a called-for shift to an upstream provision of palliative care as an overall care approach within a health equity perspective. Our research explored how nurses in psychiatry engage with aging patients and mortality to discern enactment of ethical dimensions of care. Drawing from tenets of interpretative phenomenological analysis, forensic and geriatric psychiatry registered nurses working at a mental health facility in eastern Ontario completed interviews for analysis. Nurses engaged with mortality through a process of recognition and through the affirmation of their values. The affirmed values are aligned with the palliative care approach and within an ethics of finitude lens in that their enactment is partly premised on the recognition of patients' accumulated losses related to human facticities (social, temporal, mortal). This research underscores preliminary insights on a process identifying care practices aligned with the palliative approach and possibilities for expanding upon an ethics of finitude lens.